1996
DOI: 10.1073/pnas.93.2.814
|View full text |Cite
|
Sign up to set email alerts
|

Gangliosides are neuronal ligands for myelin-associated glycoprotein.

Abstract: Nerve Nerve cell function depends upon appropriate contacts between the neuron and other cells in its immediate environment (1). These include specialized glial cells, oligodendrocytes in the central nervous system (CNS) and Schwann cells in the peripheral nervous system, which ensheathe the neuronal axon with myelin, an insulating structure of multilayered membranes (2). Myelin is required for efficient nerve impulse conduction but has other profound biological effects. The inability of nerves to regenerate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
140
2
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 268 publications
(146 citation statements)
references
References 34 publications
(27 reference statements)
3
140
2
1
Order By: Relevance
“…These results show that clustering specific gangliosides in the absence of Mag and/or Ngr is sufficient to effect inhibition. Undoubtedly, Mag can and does bind gangliosides in a highly specific manner 107 . Indeed, binding to gangliosides is likely to potentiate and augment Mag's effect by inducing clustering of the signalling molecules.…”
Section: Receptors For Inhibitors Of Axonal Growthmentioning
confidence: 99%
“…These results show that clustering specific gangliosides in the absence of Mag and/or Ngr is sufficient to effect inhibition. Undoubtedly, Mag can and does bind gangliosides in a highly specific manner 107 . Indeed, binding to gangliosides is likely to potentiate and augment Mag's effect by inducing clustering of the signalling molecules.…”
Section: Receptors For Inhibitors Of Axonal Growthmentioning
confidence: 99%
“…This terminal structure is found on some O-linked glycoproteins throughout the body, but in the mammalian brain it is much more abundant on gangliosides GD1a and GT1b (12). Direct binding studies confirmed potent and highly specific MAG binding to these gangliosides (14,34). Furthermore, mice engineered to lack the ''NeuAc ␣3 Gal ␤3 GalNAc'' terminus on gangliosides (but not on glycoproteins) displayed axon degeneration and dysmyelination similar to mice lacking MAG (15).…”
Section: Discussionmentioning
confidence: 75%
“…Neuronal gangliosides mediate communication between axons and myelin-producing cells (23)(24)(25). MAG, a myelin-associated protein found on the myelin membrane adjacent to the axon, interacts with neuronal gangliosides to stabilize axonal-myelin interactions.…”
Section: Discussionmentioning
confidence: 99%